STRATEGI GURU DALAM MENGEMBANGKAN NILAI-NILAI KARAKTER MELALUI PENGEMBANGAN KURIKULUM PAI DI SMA MUHAMMADIYAH 7 SAWANGAN - Chaerani, Hana; Rosfiani, Okta; Sendi, Rama Putra Arya; Nabilla, Raysha (FKIP Universitas Al Washliyah Medan, 2025)
Character education, vital amidst youth moral challenges, is strongly supported by Islamic Religious Education (PAI) and the Merdeka Curriculum. SMA Muhammadiyah 7 Sawangan is deeply committed to fostering students with noble character through innovative PAI curriculum. This research aims to examine PAI teachers' strategies in developing character values through PAI curriculum innovation, identifying instilled values, evaluating implementation effectiveness, designing a relevant strategy model, and analyzing supporting and inhibiting factors.This qualitative case study at SMA Muhammadiyah 7 Sawangan (March-June 2025) is unique for integrating PAI curriculum development with character strategies within a Muhammadiyah context, employing mixed methods, and focusing on digital native generations. The findings indicate interactive and character-based learning supported by conducive classroom environments, active learning dynamics, and the inculcation of religious, disciplined, tolerant, and responsible values through various methods. Comprehensive curriculum development strategies include a character-based curriculum, collaboration, and continuous evaluation, proving effective in enhancing students' character values and PAI academic achievement. In conclusion, PAI teachers' strategies at SMA Muhammadiyah 7 Sawangan successfully develop student character, though continuous improvement and development are still needed.